Effects of Different Temperatures on Storage Quality and Enzyme Activities of Fritillaria thunbergii Miq from the Soil - Xudong LIN; Yifei DONG; Jiangang LING; Lin ZHU (Shipin gongye ke-ji, 2024)
In order to investigate the effects of different storage temperatures on the storage quality and enzyme activities of Fritillaria thunbergii Miq from the soil, which were stored at 0, 5, 10 and 20 ℃ for 90 d. The changes in weight loss, sensory quality, color, hardness, total polysaccharides, alkaloids, malondialdehyde (MDA) contents, polyphenol oxidase (PPO), peroxidase (POD) and superoxide dismutase (SOD) activities of Fritillaria thunbergii Miq were explored at different storage temperatures. The results showed that the weight loss rate of Fritillaria thunbergii Miq at 0 ℃ for 90 d was only 7.17%, which was significantly lower than that at 5, 10 and 20 ℃ (9.92%, 19.77% and 30.28%) (P<0.05). The color, hardness, total polysaccharide content and total alkaloid content of Fritillaria thunbergii Miq were better maintained at 0 ℃ storage compared with 5, 10 and 20 ℃. The increment of MDA content was effectively inhibited at 0 ℃ storage, thus delaying the aging process of Fritillaria thunbergii Miq bulb. Meanwhile, the activities of PPO and POD were effectively inhibited and the maintenance of higher SOD activity at 0 ℃ storage. Compared with 5, 10 and 20 ℃, the quality of Fritillaria thunbergii Miq was best maintained in 0 ℃ storage. Thus, this study provides a methodological reference and a theoretical basis for the off-soil storage of Fritillaria thunbergii Miq.